A statistical analysis of life cycle assessment for buildings and buildings’ refurbishment research - Aseel Hussien; Ahmed Abdeen Saleem; Emad Mushtaha; Nusrat Jannat; Ahmed Al-Shammaa; Shafayat Bin Ali; Sulaf Assi; Dhiya Al-Jumeily (Ain Shams Engineering Journal, 2023)
This study aims to examine the literature related to environmental Life Cycle Assessment (LCA) for buildings and buildings' refurbishment from 1994 to 2022 by implementing a statistical analysis based on 'Web of Science' databases. LCA is viewed as a consolidated process that measures the environmental performance of buildings and their services, aiming to address the potential environmental impacts over the life cycle of buildings. A total of 1336 retrieved journal publications for LCA for buildings and 169 journal publications for LCA in building refurbishment. The articles' patterns were investigated in terms of subject categories, journals, countries, and the most highly cited articles. The findings reveal that LCA publications for buildings and building refurbishment have increased over the period 1994–2022, with China being the leading country contributing to the largest number of articles and possessing the most significant influence, followed by the USA for LCA in buildings. While Portugal is the leading country, followed by Italy, for LCA Buildings' Refurbishments. 97.08% of the publications were written in English, 2.04% in German, and 0.68% in Spanish. French and Japanese were the remaining languages, each with one publication, accounting for 0.2% of the 1336 building LCA publications. In contrast to refurbishment, LCA publications were written in only two languages, English (98.7%) and German (1.3%). Results show that the subject area differs depending on the type of LCA publication, with building LCA focusing on construction engineering while refurbishment focused on environmental topics. According to the IF, the most influential journal was renewable & sustainable energy for buildings and refurbishment LCA. However, journal distribution within LCA is still limited, and assessment methods and theme analysis still need to catch up with a clear gap in LCA in environmental impact mitigation and analysis methodologies, which will be a prominent direction of future building LCA research.